2019
DOI: 10.1093/mnras/stz281
|View full text |Cite
|
Sign up to set email alerts
|

Probing cosmic dawn: modelling the assembly history, SEDs, and dust content of selected z ∼ 9 galaxies

Abstract: The presence of spectroscopically confirmed Balmer breaks in galaxy spectral energy distributions (SEDs) at z > 9 provides one of the best probes of the assembly history of the first generations of stars in our Universe. Recent observations of the gravitationally lensed source, MACS 1149 JD1 (JD1), indicate that significant amounts of star formation likely occurred at redshifts as high as z 15. The inferred stellar mass, dust mass, and assembly history of JD1, or any other galaxy at these redshifts that exhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 59 publications
5
31
1
Order By: Relevance
“…The [O III] / [C II] emission line ratio for high redshift galaxies. Our work on MACS1149 JD1 and A2744 YD4 together with the z = 7.2 LAE (Inoue et al 2016) indicate ratios well above those seen in local metal poor dwarfs(Madden et al 2013, grey circles) as well as numerical simulations capable of predicting both lines(Katz et al 2019, black open symbols). The maximum effect of CMB attenuation is indicated by dashed lines below the current limits (see text for details).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…The [O III] / [C II] emission line ratio for high redshift galaxies. Our work on MACS1149 JD1 and A2744 YD4 together with the z = 7.2 LAE (Inoue et al 2016) indicate ratios well above those seen in local metal poor dwarfs(Madden et al 2013, grey circles) as well as numerical simulations capable of predicting both lines(Katz et al 2019, black open symbols). The maximum effect of CMB attenuation is indicated by dashed lines below the current limits (see text for details).…”
supporting
confidence: 56%
“…Likewise when studying the [Oiii]88µm/ [Cii]158µm line ratio, we find anomalously high values. We examine this line ratio with a recent hydrodynamical simulation of the ISM in early galaxies (Katz et al 2019) and suggest that a low gas-phase metallicity may not be the sole explanation for this [C II] deficit. Other hypotheses include a high ionisation parameter consistent with trends seen in UV spectroscopy of similar z > 7 sources or the suppression of neutral gas and hence [Cii]158µm emission via energetic feedback from intermittent star formation.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, Katz et al (2019) point out that strong Balmer breaks are rare in their simulations if one considers dust-free galaxies, which is consistent with our findings. In difference to the Katz et al (2019) study, we find that galaxies with Balmer breaks as strong as the one observed in JD1 are rare in the simulations at z ∼ 9, even when considering differential obscuration. This means that the main difference in our results stem from the different treatment of dust effects.…”
Section: Simulated Galaxies and Macs1149-jd1supporting
confidence: 91%
“…Thus, the effect of differential obscuration may become significantly smaller in cases where dust scattering is considered. In addition to finding an analogue to JD1, Katz et al (2019) show that they find 3 objects that exhibit strong Balmer breaks in their simulation volume. It is, however not entirely clear how likely we are to find such galaxies in their simulations when considering a larger sample of objects (especially when considering possible viewing-angle effects).…”
Section: Simulated Galaxies and Macs1149-jd1mentioning
confidence: 89%
See 1 more Smart Citation